Competition between folded and extended structures of alanylalanine (Ala-Ala) in a molecular beam. Issue 26 (14th March 2019) - Yatsyna, Vasyl; Mallat, Ranim; Gorn, Tim; Schmitt, Michael; Feifel, Raimund; Rijs, Anouk M.; Zhaunerchyk, Vitali
Abstract : Structural analysis of the neutral dipeptide Ala-Ala by action spectroscopy using IRMPD-VUV spectroscopy reveals predominance of extended structure. Abstract : We report the gas phase conformational preferences of laser desorbed Ala-Ala dipeptides probed by action spectroscopy using the IRMPD-VUV method. The molecules were internally cooled through collisional cooling in a supersonic jet environment. An IR spectrum was obtained experimentally in the spectral range of 700–1850 cm −1, and subsequently interpreted with the help of quantum chemical calculations. Although theory predicts that folded structures have lower electronic energies and, thus, are more stable at low temperatures compared to their extended (β-strand-like) counterparts, analysis of the experimental data concluded the extended conformer to be the most dominant. An explanation to this observation is discussed in this paper and rationalized in terms of collisional conformer relaxation processes occurring in the supersonic jet molecular beam.